2021
DOI: 10.1002/aelm.202100753
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Endohedral Metallofullerene Single‐Crystal Arrays for High‐Performance Field‐Effect Transistors and Photodetectors

Abstract: A structure with high crystallinity and orderly molecular packing is a requirement for high‐performance optoelectronic devices. However, growing large‐area, long‐range order, highly crystalline micro or nanostructures remains a challenge. Endohedral metallofullerenes (EMFs) are spherical π‐conjugated molecules with unique electronic structures, hence they can be easily assembled into highly ordered crystals through intermolecular π–π interactions. In this work, large‐area single‐crystal microwire arrays of M3N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…417,418 For instance, Li and coworkers prepared long-range M 3 NCC 80 (M = Sc, Lu) single-crystal microwires by utilizing a pillar-structured template, which exhibited highly sensitive photoconductivity with a response time as low as 0.1 s, and also were employed in field-effect transistors. 469 Molecular gels have been used as spatially confined templates for the growth of C 60 crystals to obtain super-long crystalline C 60 fibers and large-area 2D crystals, which were utilized as photodetectors with high performance by Liu, Fang, and coworkers. 470,471 The dice-shaped Sc 3 NCC 80 3D crystals have been utilized as a support for the Pt-catalyzed methanol oxidation by Yang and coworkers.…”
Section: Assembly Of Ordered Fullerene Materialsmentioning
confidence: 99%
“…417,418 For instance, Li and coworkers prepared long-range M 3 NCC 80 (M = Sc, Lu) single-crystal microwires by utilizing a pillar-structured template, which exhibited highly sensitive photoconductivity with a response time as low as 0.1 s, and also were employed in field-effect transistors. 469 Molecular gels have been used as spatially confined templates for the growth of C 60 crystals to obtain super-long crystalline C 60 fibers and large-area 2D crystals, which were utilized as photodetectors with high performance by Liu, Fang, and coworkers. 470,471 The dice-shaped Sc 3 NCC 80 3D crystals have been utilized as a support for the Pt-catalyzed methanol oxidation by Yang and coworkers.…”
Section: Assembly Of Ordered Fullerene Materialsmentioning
confidence: 99%
“…In 2021, Su et al demonstrated a high-performance FET utilizing EMFs containing metal nitride clusters. 56 Unlike the single metal atom cases, metal-nitride cluster EMFs exhibit icosahedral symmetry, similar to that of C 60 . Through strong π−π interactions between molecules, M 3 N@C 80 can assemble into microcrystals of various shapes in a solution.…”
Section: Organic Field-effect Transistormentioning
confidence: 98%
“…In 2021, Su et al demonstrated a high-performance FET utilizing EMFs containing metal nitride clusters . Unlike the single metal atom cases, metal-nitride cluster EMFs exhibit icosahedral symmetry, similar to that of C 60 .…”
Section: Organic Field-effect Transistormentioning
confidence: 99%
“…6,7 To date, there have been plenty of examples of morphological and structural control of FMNAs by finely tuning their preparation conditions. It was also reported that these well-defined FMNAs may exhibit unprecedented properties such as high electron carrier mobility and magnetic properties, 8,9 which are otherwise unavailable for individual molecules and amorphous aggregations. Nevertheless, there are fewer attempts to understand the deterministic relationship between the morphologies/structures of FMNAs and their physical properties.…”
Section: Introductionmentioning
confidence: 99%